2016
DOI: 10.1016/j.jhep.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10/CXCR3 signaling mobilized-regulatory T cells promote liver tumor recurrence after transplantation

Abstract: There were positive correlation among tumor recurrence, circulating Tregs and liver graft injury after human transplantation for HCC patients. The knockout of CXCL10 decreased hepatic recruitment of CXCR3 Tregs and late phase tumor recurrence after hepatic IR injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 43 publications
(59 reference statements)
1
78
0
Order By: Relevance
“…It has been reported that regulatory T-cells initiate recruitment and suppressive function via a CCL1 dependent pathway (23,24). In addition, the CXCR3 signaling directly induces the mobilization and recruitment of Tregs (25). Therefore, the Helios-1 may function as the transcription factor for regulatory T-cells by targeting the CCL1 and CXCR3 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that regulatory T-cells initiate recruitment and suppressive function via a CCL1 dependent pathway (23,24). In addition, the CXCR3 signaling directly induces the mobilization and recruitment of Tregs (25). Therefore, the Helios-1 may function as the transcription factor for regulatory T-cells by targeting the CCL1 and CXCR3 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Marginal liver grafts are probably more susceptible to ischemia/reperfusion injury (IRI) after liver transplantation . Early phase liver graft injury is known to trigger a series of inflammatory cascades that consequentially activate several immune cells with important implications in graft injury and tumor recurrence …”
Section: Impact Of Liver Graft Injury On Cancer Recurrencementioning
confidence: 99%
“…Recently, increasing evidence demonstrated that inflammatory signaling cascades activated by graft injury orchestrated regional immune regulation and cancer recurrence. We reported that posttransplant inflammatory responses mobilize more circulatory regulatory T cells (Tregs), which promote late phase tumor recurrence after liver transplantation . More circulating Tregs together with the activation of chemokine (C‐X‐C motif) ligand 10 (CXCL10)/chemokine (C‐X‐C motif) receptor 3 (CXCR3) signaling can be detected in the recipients with a small‐for‐size liver graft and tumor recurrence.…”
Section: Impact Of Liver Graft Injury On Cancer Recurrencementioning
confidence: 99%
See 2 more Smart Citations